Preparation method of high-dispersion lamellar ZSM-5 molecular sieve
Through a preparation method of high-dispersed sheet-like ZSM-5 molecular sieve, the problems of diffusion limitation in traditional ZSM-5 molecular sieve are solved, and high-efficiency and low-cost preparation is achieved, which significantly improves catalytic activity and stability. sex.
Patent Information
- Application Number
- CN202411665990.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
In the catalysis and separation process, traditional ZSM-5 molecular sieve has problems such as limited diffusion, low conversion rate, poor selectivity of target products and short catalytic life.
Using a high-dispersible flake ZSM-5 molecular sieve preparation method, the tetrapropyl ammonium hydroxide solution, deionized water, silicon source and seed crystallization and calcination under specific conditions, the synthesis was successfully carried out. ZSM-5 nanosheet molecular sieve with short b-axis and controllable sizes.
The ZSM-5 molecular sieve with high crystallinity and high purity has good dispersion and catalytic activity, significantly improving the reactivity, selectivity and stability, while reducing the preparation cost and environmental pollution risk.
Smart Images

Figure CN119390088A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of molecular sieve preparation, and in particular to a method for preparing highly dispersed flaky ZSM-5 molecular sieve. Background Art
[0002] ZSM-5 molecular sieve is a microporous zeolite developed by Mobil in the 1970s with an MFI topological structure. Its unique three-dimensional pore structure, excellent physical and chemical properties, and adjustable silicon-aluminum ratio give ZSM-5 molecular sieve excellent product selectivity, suitable acidity, large specific surface area and pore volume, and good hydrothermal stability. This makes ZSM-5 widely used in oil refining and petrochemical fields such as catalytic cracking, alkylation, isomerization and disproportionation, greatly promoting the development of the petrochemical industry.
[0003] Although the synthesis and application of ZSM-5 zeolites have made significant progress in the past few decades, the diffusion limitation caused by its long micropore channels is still prominent. This diffusion limitation not only reduces the utilization rate of the active volume of the zeolite, but also limits the transport efficiency of molecules in the catalytic and separation processes, especially in reactions that are severely limited by diffusion. Therefore, how to solve the problems of diffusion limitation, low conversion rate, poor selectivity of target products and short catalytic life in traditional ZSM-5 zeolites has become the focus of current research.
[0004] To address the above problems, researchers have conducted extensive research on the preparation of short-pore-length flaky ZSM-5 molecular sieves. Flaky ZSM-5 molecular sieves combine the dual advantages of multi-level pore molecular sieves and nano-molecular sieves, retaining the excellent catalytic, adsorption and shape-selective properties of microporous molecular sieves, and improving molecular diffusion performance by reducing pore length, significantly improving reaction activity and stability, making it one of the materials with great research and application potential.
[0005] Regarding the synthesis of flaky ZSM-5 molecular sieves, there are currently several main strategies: Post-treatment of layered zeolite precursor method: M. Choi et al. successfully prepared single-layer ZSM-5 nanosheets with a thickness of only 2 nm through post-treatment techniques such as pillaring and exfoliation. However, this method is complex, has low yield and is difficult to achieve large-scale synthesis [Reference: M. Choi, et al. Nature, 2009, 461, 246-249].
[0006] Template method: Tsapatsis et al. synthesized nanosheets with a thickness of 2 nm using template agents. This method effectively reduced diffusion limitations, but the template agents are expensive and difficult to recycle, limiting their large-scale application [Reference: M. Tsapatsis, et al. Nature, 2017, 543, 690-694].
[0007] Chemical etching method: Liu Yi et al. anisotropically etched ZSM-5 molecular sieves with TPAOH solution and successfully prepared monodisperse flake molecular sieves with a thickness of 25 nm. Although this method is simple to operate, it has poor effect on low-silicon samples and the etching conditions are relatively harsh [reference: Y. Liu, et al. Sci. Adv., 2020, 6, eaay5993].
[0008] Additive-assisted method: Patents CN106542544A and CN105523569A introduce the synthesis of thin-sheet ZSM-5 molecular sieves using bispiperidone alkylene cations and other additives, but it is difficult to control the pore length of the sample to below 100 nm [Reference: CN106542544A, CN105523569A].
[0009] Low-temperature synthesis method: Patent CN108275697B reports a method for synthesizing ZSM-5 nanosheets under low-temperature conditions using fluorides, but fluorides are highly toxic and corrosive, which severely limits their industrial application [Reference: CN108275697B].
[0010] In summary, the current synthesis technology of sheet ZSM-5 zeolite still faces some key challenges, including difficulty in precisely controlling thickness, use of toxic chemicals, long synthesis cycle and high cost. Therefore, the development of green, efficient and low-cost preparation strategies is of great significance for the large-scale application of ZSM-5 zeolite in industry. Summary of the invention
[0011] According to an embodiment of the present invention, a method for preparing highly dispersed flaky ZSM-5 molecular sieve is provided, which is used to solve the problem raised by the above background technology.
[0012] In a first aspect of the present invention, a method for preparing highly dispersed flaky ZSM-5 molecular sieve is provided.
[0013] The preparation method of the highly dispersed flaky ZSM-5 molecular sieve comprises: S1. taking a tetrapropylammonium hydroxide solution with a mass fraction of 25%, adding deionized water to the tetrapropylammonium hydroxide solution for dilution. The tetrapropylammonium hydroxide solution and the deionized water are uniformly mixed to obtain a solution A. Tetraethyl orthosilicate is added to the solution A, and the solution is stirred under water bath conditions to promote complete hydrolysis of the tetraethyl orthosilicate, and the solution containing the tetraethyl orthosilicate is de-alcoholized. After the de-alcoholization is completed, crystallization is performed to obtain a seed solution.
[0014] S2. Mix tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 to obtain solution B.
[0015] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0016] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0017] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0018] S6. Add the deionized water containing the dissolved additive to the solution C in step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0019] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0020] Preferably, in the water bath conditions of step S1, the water bath temperature is 35° C., the alcohol removal temperature is 45° C., and the alcohol removal time is 6 hours; the crystallization temperature is 50-90° C., and the crystallization time is 36-120 hours.
[0021] Preferably, the template in step S2 is 25% by mass of tetrapropylammonium hydroxide solution, n-butylamine, tetrapropylammonium bromide or 1; the silicon source is tetraethyl orthosilicate, silica sol, white carbon black, water glass and solid silica gel.
[0022] Preferably, the aluminum source in step S3 is aluminum chloride hexahydrate, sodium aluminate, aluminum nitrate, aluminum hydroxide or aluminum sulfate.
[0023] Preferably, the stirring time in step S4 is 0.5 to 1 h.
[0024] Preferably, the additive in step S5 is ammonium bicarbonate, ammonium sulfate, ammonium carbonate, ammonium bisulfate, ethylenediamine, ethylamine, ammonium chloride, urea or ammonium nitrate.
[0025] Preferably, in step S6, the stirring time is 0.5 h, the crystallization temperature is 90-170° C., and the crystallization time is 3-72 h.
[0026] Preferably, the drying temperature of the drying treatment in step S7 is 80° C., the drying time is 12 h, the roasting temperature is 540° C., and the roasting time is 6 h.
[0027] Preferably, the mass ratio of the template: silicon source: aluminum source: additive: seed crystal: water is (0.72~2.92): (6.3~8.0): (0.16~0.32): (0.53~0.63): (0.025~6.2): 60.94.
[0028] Preferably, step S2 does not contain tetrapropylammonium hydroxide solution.
[0029] One or more technical solutions provided in this application have at least the following technical effects or advantages: The present invention provides a method for preparing highly dispersed flaky ZSM-5 molecular sieves, and successfully synthesizes ZSM-5 nanosheet molecular sieves with a short b-axis and controllable size. Compared with the prior art, the present invention has the following beneficial effects: First, according to the X-ray diffraction (XRD) test results, the synthesized thin-flaked ZSM-5 molecular sieve exhibited typical MFI structural characteristic diffraction peaks, indicating that it has high crystallinity and high purity, proving the superiority of the preparation process. Secondly, the results of scanning electron microscopy (SEM) observations showed that the molecular sieve presented a regular and uniform flaky morphology and had good dispersibility, which provided an important guarantee for its stability in applications such as catalysis and adsorption. In addition, transmission electron microscopy (TEM) observations confirmed that the ZSM-5 molecular sieve had an ultra-thin flaky structure, and the b-axis thickness could be controlled at about 20 nm. This ultra-thin structure significantly reduces the diffusion resistance, thereby improving the catalytic activity, selectivity and stability of the molecular sieve in actual industrial applications.
[0030] The data of nitrogen physical adsorption experiments further confirmed that the thin-sheet ZSM-5 molecular sieve has a large specific surface area. High specific surface area is closely related to reaction activity, which can significantly increase the contact probability between reactants and active centers, thereby greatly improving its performance in catalytic reactions. In addition, combined with its ultra-thin morphology, this molecular sieve exhibits superior performance in a variety of chemical reactions and material applications.
[0031] More importantly, this preparation method does not require the use of organic templates, which reduces the preparation cost and eliminates the potential risk of environmental pollution, thus helping to achieve green and environmentally friendly industrial production.
[0032] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the embodiments of the present invention, nor are they intended to limit the scope of the present invention. Other features of the present invention will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The above and other features, advantages and aspects of the embodiments of the present invention will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements, wherein: Figure 1 This is a TEM photograph of the seed solution synthesized in Example 1 of the present invention.
[0034] Figure 2 This is the XRD spectrum of the flaky ZSM-5 molecular sieve synthesized in Example 1 of the present invention.
[0035] Figure 3 This is a SEM photograph of the flaky ZSM-5 molecular sieve synthesized in Example 1 of the present invention.
[0036] Figure 4 This is a TEM photograph of the flaky ZSM-5 molecular sieve synthesized in Example 1 of the present invention.
[0037] Figure 5 This is a nitrogen physical adsorption-desorption isotherm diagram of the flaky ZSM-5 molecular sieve synthesized in Example 1 of the present invention.
[0038] Figure 6 This is the XRD spectrum of the flaky ZSM-5 molecular sieve synthesized in Example 2 of the present invention.
[0039] Figure 7 This is a SEM photograph of the flaky ZSM-5 molecular sieve synthesized in Example 2 of the present invention.
[0040] Figure 8 This is a SEM photograph of the flaky ZSM-5 molecular sieve synthesized in Example 3 of the present invention.
[0041] Fig. 9 This is a TEM photograph of the seed solution synthesized in Example 7 of the present invention.
[0042] Fig.10 This is a SEM photograph of the flaky ZSM-5 molecular sieve synthesized in Example 7 of the present invention.
[0043] Fig.11 This is a SEM photograph of the flaky ZSM-5 molecular sieve synthesized in Example 12 of the present invention. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In addition, the term "and / or" in this article is only a description of the association relationship between the associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0046] Embodiment 1 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0047] Take 70 g of 25% tetrapropylammonium hydroxide solution, add 30 g of deionized water to dilute it; mix the tetrapropylammonium hydroxide solution and deionized water evenly to obtain solution A; add 50 g of tetraethyl orthosilicate to solution A, keep it at 35 ℃ under water bath conditions, stir for 6 hours to promote the complete hydrolysis of tetraethyl orthosilicate, and then it will be a clear and transparent solution. After the tetraethyl orthosilicate is completely hydrolyzed, increase the water bath temperature to 45 ℃ to remove alcohol, and the alcohol removal time is 6 hours; after the alcohol removal is completed, seal the solution under constant temperature conditions for crystallization; the crystallization temperature is 80 ℃, and the crystallization time is 36 hours to obtain a seed solution.
[0048] Among them, the prepared seed crystal morphology is spherical particles, and the transmission electron microscope image is as follows Figure 1 As shown, the diameter size is 20~50 nm.
[0049] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water to dilute, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0050] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0051] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0052] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0053] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0054] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0055] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0056] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0057] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 3 h to obtain a crystallized sample.
[0058] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0059] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0060] like Figures 2~5 The calcined samples were characterized by XRD. Figure 2 The synthesized ZSM-5 molecular sieve has typical MFI characteristic diffraction peaks, high crystallinity and no impurities.
[0061] The samples were characterized by scanning electron microscopy, and the SEM images were as follows: Figure 3 As shown, the results show that the synthesized molecular sieve has a regular flake morphology, the sample has excellent dispersion and uniform size, with a length X of about 600 nm and a width Y of about 150 nm.
[0062] The sample was characterized by transmission electron microscopy to observe the size of its thickness Z. The TEM image is shown in Figure 4 As shown, the results show that the thickness Z of the sample is around 20 nm.
[0063] The samples were subjected to nitrogen physical adsorption test, such as Figure 5 As shown, the specific surface area of the sample is 427 m 2 / g, with a total pore volume of 0.5 cm 3 / g.
[0064] The above results confirm that the method of the present invention can successfully prepare highly dispersed thin-flaked ZSM-5 molecular sieves with a thickness of only 20 nm, which have excellent physical structural characteristics such as large specific surface area, high pore volume, and short diffusion length, which can greatly improve the contactability between reactants and active centers and improve reaction performance. In addition, compared with conventional ZSM-5 synthesis, ZSM-5 nanosheets can complete crystallization in only 3 hours, greatly reducing energy consumption and time costs. More importantly, it is confirmed that ammonium bicarbonate can be used as an additive to successfully prepare highly dispersed thin-flaked ZSM-5 molecular sieves, which is not reported in other reports.
[0065] Embodiment 2 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0066] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, at which time a clear and transparent solution was obtained. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0067] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water to dilute, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0068] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0069] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0070] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0071] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0072] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0073] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0074] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0075] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 90 °C for 72 h to obtain a crystallized sample.
[0076] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0077] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0078] like Figure 6 As shown, the obtained ZSM-5 nanosheets were characterized by X-ray diffraction (XRD) as pure phase ZSM-5 molecular sieve with good crystallinity; Figure 7 As shown, scanning electron microscopy characterization confirmed that the sample had a flake-like morphology, good dispersion and uniform size.
[0079] The advantage of this embodiment is that the synthesis of sheet ZSM-5 molecular sieve can be achieved at a low temperature of 90 ° C. Usually, the synthesis of ZSM-5 molecular sieve needs to be carried out at 150-180 ° C, which is conducive to reducing the energy consumption of synthesis. In addition, since the saturated vapor pressure of water at 90 ° C is less than 0.1Mpa, the pressure resistance requirement for crystallization equipment is lower, and plastic containers can be used for crystallization, which expands the diversification of equipment.
[0080] Embodiment 3 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0081] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0082] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water to dilute, then add 8.0 g of tetraethyl orthosilicate and 0.025 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0083] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0084] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0085] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0086] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0087] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0088] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0089] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0090] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 12 h to obtain a crystallized sample.
[0091] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0092] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 90 nm was obtained.
[0093] The samples were characterized by scanning electron microscopy, and the SEM images were as follows: Figure 8 As shown, the results show that the synthesized molecular sieve has a regular flake morphology, the sample has excellent dispersion, uniform size, a length X of about 500 nm, a width Y of about 200 nm, and a thickness Z of about 90 nm.
[0094] In this embodiment, the amount of seed crystal added is adjusted from 50 wt.% in the first embodiment to 0.2 wt.% to achieve the synthesis of ZSM-5 nanosheets, which has the advantage that the thickness of the ZSM-5 nanosheets can be adjusted. Since the thickness direction of ZSM-5 is the direction of its straight channel, the controllable adjustment of the straight channel length is conducive to achieving a variety of reaction purposes.
[0095] Embodiment 4 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0096] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0097] S2. Mixing deionized water, a silicon source and the seed solution prepared in step S1 to obtain a solution B; Take 30.94 g of deionized water, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, and stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, at which time it is a clear and transparent solution.
[0098] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0099] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0100] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0101] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0102] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0103] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0104] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0105] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 12 h to obtain a crystallized sample.
[0106] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0107] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0108] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0109] The advantage of this embodiment is that no organic template is introduced during the preparation process, and the template-free synthesis of flaky ZSM-5 molecular sieves is achieved by adding a seed solution. Usually, the synthesis of ZSM-5 molecular sieves requires a large amount of organic template, which is conducive to reducing preparation costs and reducing environmental pollution problems.
[0110] Embodiment 5 S1. Prepare seed solution.
[0111] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0112] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 0.96 g of tetrapropylammonium bromide, add 25.56 g of deionized water to dissolve it, then add 7.68 g of silica sol and 2.48 g of seed solution, and stir in a water bath at 35 °C for 2 h. At this time, a clear and transparent solution is obtained.
[0113] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0114] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0115] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0116] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0117] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0118] 0.60 g of the additive was diluted in 15 g of deionized water, wherein the additive was ethylamine.
[0119] S6. Add deionized water containing additives to the white solution C in step S4 and stir, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0120] Deionized water containing ethylamine was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170° C. for 12 h to obtain a crystallized sample.
[0121] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0122] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0123] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0124] The advantage of this embodiment is that cheap silica sol is used instead of ethyl orthosilicate to synthesize ZSM-5 nanosheets, which is conducive to reducing the preparation cost. However, the template agent needs to be changed to tetrapropylammonium bromide, and the additive needs to be changed to ethylamine to control the growth of nanosheets and provide an alkaline environment.
[0125] Embodiment 6 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0126] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0127] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water for dilution, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0128] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0129] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0130] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0131] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0132] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0133] 0.53 g of additives were dissolved in 15 g of deionized water, wherein the additives were ammonium sulfate and ammonium chloride.
[0134] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0135] Deionized water in which ammonium sulfate and ammonium chloride are dissolved is added to the white solution C in step S4 and stirred for 0.5 h. The mixture is then placed in a 100 mL crystallization kettle and crystallized at 170° C. for 12 h to obtain a crystallized sample.
[0136] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0137] The crystallized sample was subjected to solid-liquid separation, dried at 80°C for 12 hours, and then calcined at a temperature of 540°C for 6 hours; and finally a flaky ZSM-5 molecular sieve with a thickness of 20 nm was obtained.
[0138] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0139] This embodiment uses ammonium sulfate and ammonium chloride instead of ammonium bicarbonate solution to achieve the synthesis of ZSM-5 nanosheets, expanding the synthesis range.
[0140] Embodiment 7 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0141] Specifically, 70 g of a 25% mass fraction tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 60 °C, and the crystallization time was 120 h, and a seed solution was obtained.
[0142] Among them, the prepared seed crystal morphology is spherical particles, and the transmission electron microscope image is as follows Fig. 9 As shown, the diameter size is 20~30 nm.
[0143] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water to dilute, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0144] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0145] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0146] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0147] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0148] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0149] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0150] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0151] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 12 h to obtain a crystallized sample.
[0152] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0153] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0154] The samples were characterized by scanning electron microscopy, and the SEM images were as follows: Fig.10 As shown, the results show that the synthesized molecular sieve has a regular flake morphology, the sample has excellent dispersion and uniform size, with a length X of about 400 nm, a width Y of about 200 nm, and a thickness Z of about 30 nm.
[0155] This embodiment adjusts the crystal size of ZSM-5 nanosheets by changing the crystallization temperature and time of the seed solution. This method is simpler, faster and more efficient in crystal regulation.
[0156] Embodiment 8 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0157] Specifically, 70 g of a 25% mass fraction tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 90 °C, and the crystallization time was 24 h, and a seed solution was obtained.
[0158] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 4.37 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water for dilution, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir for 2 h in a water bath at 35 °C to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0159] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0160] 0.96 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0161] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0162] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0163] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0164] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0165] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0166] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 48 h to obtain a crystallized sample.
[0167] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0168] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0169] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0170] In this embodiment, the synthesis of ZSM-5 nanosheets with a low silicon-to-aluminum ratio is achieved by adjusting the addition amount of the template and the aluminum source.
[0171] Embodiment 9 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0172] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0173] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water to dilute, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0174] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0175] 0.21 g of aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is sodium aluminate and aluminum hydroxide.
[0176] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0177] Deionized water in which sodium aluminate and aluminum hydroxide are dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0178] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0179] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0180] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0181] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 12 h to obtain a crystallized sample.
[0182] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0183] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0184] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0185] In this embodiment, sodium aluminate and aluminum hydroxide are used instead of aluminum chloride to synthesize ZSM-5 nanosheets, which has the advantage of reducing the corrosion of chloride ions in the solution to the equipment.
[0186] Embodiment 10 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0187] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0188] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 0.45 g of 1.6-hexanediamine, add 30.94 g of deionized water to dissolve and dilute, then add 8.0 g of tetraethyl orthosilicate and 2.48 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0189] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0190] 0.16 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum nitrate nonahydrate.
[0191] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0192] Deionized water in which aluminum nitrate nonahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0193] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0194] 0.61 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium nitrate.
[0195] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0196] Deionized water in which ammonium nitrate is dissolved is added to the white solution C in step S4 and stirred for 0.5 h. The mixture is then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 48 h to obtain a crystallized sample.
[0197] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0198] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0199] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0200] In this embodiment, 1.6-hexanediamine is used instead of tetrapropylammonium hydroxide as an organic template to prepare ZSM-5 nanosheets. Since the ZSM-5 molecular sieve synthesized by 1.6-hexanediamine has the characteristic of uniform aluminum distribution, the position of the acidic site on the ZSM-5 nanosheet is regulated.
[0201] Embodiment 11 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0202] Specifically, 70 g of a 25% tetrapropylammonium hydroxide solution was taken, and 30 g of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 50 g of tetraethyl orthosilicate was added to solution A, and the solution was kept at 35 °C in a water bath and stirred for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained at this time. After the tetraethyl orthosilicate was completely hydrolyzed, the water bath temperature was increased to 45 °C for alcohol removal, and the alcohol removal time was 6 h; after the alcohol removal was completed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0203] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 0.72 g of n-butylamine, add 30.94 g of deionized water to dilute, then add 6.3 g of water glass, 1.2 g of white carbon black and 6.20 g of seed solution, stir for 2 h in a water bath at 35 °C to mix the solution evenly.
[0204] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0205] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0206] S4. Add deionized water containing the aluminum source to the solution in step S2 and stir to obtain a white solution C.
[0207] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.5 h to obtain a white solution C.
[0208] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0209] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0210] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0211] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 48 h to obtain a crystallized sample.
[0212] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0213] The crystallized sample was subjected to solid-liquid separation, dried at 80°C for 12 h, and then calcined at 540°C for 6 h; ultimately, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0214] The obtained ZSM-5 nanosheets were characterized as pure phase ZSM-5 molecular sieve by X-ray diffraction (XRD), and scanning electron microscopy showed that the sample had a good degree of crystallization, a thin flake morphology, good dispersion, and uniform size.
[0215] The advantage of this embodiment is that n-butylamine is used instead of tetrapropylammonium hydroxide as an organic template, and water glass and white carbon black are used instead of ethyl orthosilicate as a silicon source. Since n-butylamine, water glass and white carbon black are relatively cheap, and n-butylamine is easily recyclable, the preparation cost can be effectively reduced.
[0216] Embodiment 12 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0217] Specifically, 140 kg of a 25% tetrapropylammonium hydroxide solution was taken, and 60 kg of deionized water was added to the tetrapropylammonium hydroxide solution for dilution; the tetrapropylammonium hydroxide solution and the deionized water were mixed evenly to obtain solution A; 100 kg of tetraethyl orthosilicate was added to solution A, and the solution was stirred at 35 °C for 6 h to completely hydrolyze the tetraethyl orthosilicate, and a clear and transparent solution was obtained. After the tetraethyl orthosilicate was completely hydrolyzed, the solution was sealed under constant temperature conditions for crystallization; the crystallization temperature was 80 °C, and the crystallization time was 36 h, and a seed solution was obtained.
[0218] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 328.0 kg of 25% tetrapropylammonium hydroxide solution, add 1827.9 kg of deionized water for dilution, then add 1200.0 kg of ethyl orthosilicate and 190.0 kg of seed solution, stir at 35 °C for 2 h to completely hydrolyze the ethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0219] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0220] 21.1 kg of aluminum source is dissolved in 1037.0 kg of deionized water, wherein the aluminum source is aluminum sulfate.
[0221] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0222] Deionized water in which aluminum sulfate is dissolved is added to the clarified solution in step S2 and stirred for 2 hours to obtain a white solution C.
[0223] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0224] 69.1 kg of an additive is dissolved in 600.0 kg of deionized water, wherein the additive is urea.
[0225] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0226] The deionized water with urea dissolved in it was added to the white solution C in step S4 and stirred for 2 h. 3 The crystallized sample was obtained by crystallization at 170 °C for 72 h in an industrial crystallization reactor.
[0227] S7. Wash, filter, dry and calcine the crystallized sample to obtain a flaky ZSM-5 molecular sieve.
[0228] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h. Finally, a flaky ZSM-5 molecular sieve with a thickness of about 30 nm was obtained.
[0229] The obtained ZSM-5 nanosheets were characterized by X-ray diffraction (XRD) as pure phase ZSM-5 molecular sieve. The sample was characterized by scanning electron microscopy, and the SEM image is shown in Fig.11 As shown, the results show that the synthesized molecular sieve has a regular flake morphology, the sample has excellent dispersion and uniform size, with a length X of about 400 nm, a width Y of about 150 nm, and a thickness Z of about 33 nm.
[0230] This embodiment uses industrial 8m 3 The crystallization reactor was used to achieve large-scale synthesis of ZSM-5 nanosheets, which confirmed the feasibility of this synthesis strategy in industrial scale-up synthesis and laid the foundation for its further application in industrial-scale catalytic reactions and adsorption separations.
[0231] Embodiment 13 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0232] Take 70 g of 25% tetrapropylammonium hydroxide solution, add 30 g of deionized water to dilute it; mix the tetrapropylammonium hydroxide solution and deionized water evenly to obtain solution A; add 50 g of tetraethyl orthosilicate to solution A, keep it at 35 ℃ under water bath conditions, stir for 6 hours to promote the complete hydrolysis of tetraethyl orthosilicate, and then it will be a clear and transparent solution. After the tetraethyl orthosilicate is completely hydrolyzed, increase the water bath temperature to 45 ℃ to remove alcohol, and the alcohol removal time is 6 hours; after the alcohol removal is completed, seal the solution under constant temperature conditions for crystallization; the crystallization temperature is 80 ℃, and the crystallization time is 36 hours to obtain a seed solution.
[0233] Among them, the prepared seed crystal morphology is spherical particles, and the transmission electron microscope image is as follows Figure 1 As shown, the diameter size is 20~50 nm.
[0234] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water for dilution, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze tetraethyl orthosilicate, and then a clear and transparent solution is obtained. Tetraethyl orthosilicate can be replaced by silica sol, white carbon black, water glass or solid silica gel.
[0235] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0236] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0237] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0238] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 1 hour to obtain a white solution C.
[0239] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0240] 0.63 g of an additive was dissolved in 15 g of deionized water, wherein the additive was ammonium bicarbonate.
[0241] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0242] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 3 h to obtain a crystallized sample.
[0243] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0244] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0245] Embodiment 14 A method for preparing highly dispersed flaky ZSM-5 molecular sieve comprises the following steps: S1. Prepare seed solution.
[0246] Take 70 g of 25% tetrapropylammonium hydroxide solution, add 30 g of deionized water to dilute it; mix the tetrapropylammonium hydroxide solution and deionized water evenly to obtain solution A; add 50 g of tetraethyl orthosilicate to solution A, keep it at 35 ℃ under water bath conditions, stir for 6 hours to promote the complete hydrolysis of tetraethyl orthosilicate, and then it will be a clear and transparent solution. After the tetraethyl orthosilicate is completely hydrolyzed, increase the water bath temperature to 45 ℃ to remove alcohol, and the alcohol removal time is 6 hours; after the alcohol removal is completed, seal the solution under constant temperature conditions for crystallization; the crystallization temperature is 80 ℃, and the crystallization time is 48 hours to obtain a seed solution.
[0247] Among them, the prepared seed crystal morphology is spherical particles, and the transmission electron microscope image is as follows Figure 1 As shown, the diameter size is 20~50 nm.
[0248] S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; Take 2.92 g of 25% tetrapropylammonium hydroxide solution, add 30.94 g of deionized water to dilute, then add 8.0 g of tetraethyl orthosilicate and 6.20 g of seed solution, stir in a water bath at 35 °C for 2 h to completely hydrolyze the tetraethyl orthosilicate, and the solution becomes a clear and transparent solution.
[0249] S3. Add an aluminum source into deionized water to dissolve the aluminum source in the deionized water.
[0250] 0.32 g of an aluminum source is dissolved in 15 g of deionized water, wherein the aluminum source is aluminum chloride hexahydrate.
[0251] S4. Add deionized water containing the aluminum source to the clarified solution in step S2 and stir to obtain a white solution C.
[0252] Deionized water in which aluminum chloride hexahydrate is dissolved is added to the clarified solution in step S2 and stirred for 0.7 h to obtain a white solution C.
[0253] S5. Add the additive to the deionized water to dissolve the additive in the deionized water.
[0254] 0.63 g of an additive is dissolved in 15 g of deionized water, wherein the additive is ammonium bicarbonate, ammonium sulfate, ammonium carbonate, ammonium bisulfate, ethylenediamine, ethylamine, ammonium chloride, urea or ammonium nitrate.
[0255] S6. Add the deionized water containing the dissolved additive to the white solution C of step S4 and stir the solution, then put the solution into a crystallization kettle for crystallization to obtain a crystallized sample.
[0256] Deionized water in which ammonium bicarbonate was dissolved was added to the white solution C in step S4 and stirred for 0.5 h. The mixture was then placed in a 100 mL crystallization kettle and crystallized at 170 °C for 12 h to obtain a crystallized sample.
[0257] S7. Dry the crystallized sample and then calcine it to obtain a flaky ZSM-5 molecular sieve.
[0258] The crystallized sample was subjected to solid-liquid separation, dried at 80 °C for 12 h, and then calcined at 540 °C for 6 h; finally, a flaky ZSM-5 molecular sieve with a thickness of 30 nm was obtained.
[0259] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing highly dispersed flaky ZSM-5 molecular sieve, characterized in that: The following steps are involved: S1. Take a 25% mass fraction of tetrapropylammonium hydroxide solution, add deionized water to the tetrapropylammonium hydroxide solution to dilute it; mix the tetrapropylammonium hydroxide solution and deionized water evenly to obtain solution A; add tetraethyl orthosilicate to solution A, stir under water bath conditions to promote complete hydrolysis of tetraethyl orthosilicate, and crystallize solution A containing tetraethyl orthosilicate to obtain a seed solution; S2. The tetrapropylammonium hydroxide solution, deionized water, a silicon source and the seed solution prepared in step S1 are mixed to obtain a solution B; S3. adding an aluminum source to deionized water to dissolve the aluminum source in the deionized water; S4. The deionized water containing the dissolved aluminum source is added to the clarified solution in step S2 and stirred to obtain a white solution C; S5. Adding the additive to deionized water to dissolve the additive in the deionized water; S6. The deionized water containing the dissolved additive is added to the white solution C of step S4 and stirred, and then the solution is placed in a crystallization reactor for crystallization to obtain a crystallized sample; S7. Wash, separate, dry and calcine the crystallized sample to obtain a flaky ZSM-5 molecular sieve.
2. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: In the step S1, the solution A containing tetraethyl orthosilicate is dealcoholized before crystallization, and the dealcoholization temperature is 45°C and the dealcoholization time is 6 hours. The water bath temperature of the water bath condition in the step S1 is 35°C, the crystallization temperature is 50-90°C, and the crystallization time is 36-120 hours.
3. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: The template in step S2 is 25% by mass of tetrapropylammonium hydroxide solution, n-butylamine, tetrapropylammonium bromide or ethylamine; the silicon source is tetraethyl orthosilicate, silica sol, white carbon black, water glass and solid silica gel.
4. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: In step S3, the aluminum source is aluminum chloride hexahydrate, sodium aluminate, aluminum nitrate, aluminum hydroxide or aluminum sulfate.
5. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: The stirring time in step S4 is 0.5-1h.
6. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: In step S5, the additive is ammonium bicarbonate, ammonium sulfate, ammonium carbonate, ammonium bisulfate, ethylenediamine, ethylamine, ammonium chloride, urea or ammonium nitrate.
7. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: In step S6, the stirring time is 0.5 h, the crystallization temperature is 90-170° C., and the crystallization time is 3-72 h.
8. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: The drying temperature of the drying treatment in step S7 is 80° C., the drying time is 12 hours, the roasting temperature is 540° C., and the roasting time is 6 hours.
9. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: The mass ratio of the template: silicon source: aluminum source: additive: seed crystal: water is (0.72-2.92): (6.3-8.0): (0.16-0.32): (0.53-0.63): (0.025-6.2): 60.
94.
10. The method for preparing highly dispersed flaky ZSM-5 molecular sieve according to claim 1, characterized in that: The step S2 does not contain tetrapropylammonium hydroxide solution.
Citation Information
Patent Citations
Preparation method of laminar ZSM-5 molecular sieve
CN106542544A
A method for synthesizing ultrathin ZSM-5 molecular sieve nanosheets under low temperature and ambient pressure.
CN108275697B
Lamellar ZSM-5 molecular sieve and synthesis method thereof
CN105523569A
Method for preparing nanosheet ZSM-5 molecular sieve and application of nanosheet ZSM-5 molecular sieve
CN116854106A
Synthesis method of hierarchical pore ZSM-5 molecular sieve nanosheet with controllable b-axis thickness
CN117142484A